Knowledge and attitude towards antiretroviral therapy and adherence pattern of HIV patients in southwest Nigeria - Kasumu, Latifat; Balogun, Mobolanle (International Journal of Infection Control, 2014)
Strict adherence to highly active antiretroviral therapy remains a challenge that has important implications for treatment success. The aim of this study was to assess the knowledge, attitude and adherence pattern of antiretroviral therapy (ART) among HIV patients attending an adult antiretroviral clinic in a tertiary health facility in Lagos, southwest Nigeria. Data was collected using an interviewer-administered questionnaire on 361 patients who were selected by systematic sampling method. This study showed that 83.1% of respondents had good knowledge about ART with the more educated having significantly better knowledge (p<0.05), 98.1% had positive attitude towards ART and most of them had positive perception about their healthcare providers across most of the areas asked. The self-reported adherence level was 78.4% and older age was significantly associated with good adherence (p<0.05). A third of the respondents who missed doses did so because they were away from home. Further emphasis on good adherence during counselling sessions especially to younger patients, continuous use of reminders and use of inconspicuous pillboxes when patients are away from home are recommended.